A new genus Bongotarsonemus with two new species of tarsonemid (Acari: Heterostigmata) mites discovered from the Himalayan forests of West Bengal, India - Mondal, Priyankar; Karmakar, Krishna (Zootaxa, 2021)
Bongotarsonemus unicornus gen. nov., sp. nov. (Tarsonemidae: Tarsoneminae) is described from adult females and males collected on leaves of Sweet Cherry, Prunus avium L. (Rosaceae). Another species, Bongotarsonemus bicornus sp. nov. is described from adult females collected on leaves of a mountain fern Arthromeris wallichiana (Spreng.) Ching (Polypodiaceae). Both species were collected from the Himalayan forests of Darjeeling district in the State of West Bengal, India. Adult females of this new genus are unusual in having a median raised section of the prodorsum which is delimited by elongated tubercles bearing setae v1 and sometimes sc2. This area is ornamented with sclerotized ridges or elevated strial thickenings; and has a single or bifurcated spear-shaped horn between bases of setae v1. The new genus also has a characteristically bipartite sejugal apodeme and seta d on tibia I often reaching beyond the claw. Adult males are characterized by seta sc2 subequal to sc1; tarsus II with baciliform seta pl'' longer than half the length of the segment, and a conspicuously enlarged solenidion on tarsus IV. Both sexes are unique in having a fish-hook shaped claw on leg I with an elongated shank and strongly curved apex, and seta l' on femur I plumose.